SMART APPS CREATOR (SAC) LEARNING MEDIA TO IMPROVE SCIENCE LITERACY OF ELEMENTARY SCHOOL STUDENT - Kurniasih, Tri; Suryandari, Kartika Chrysti; Chumdari, Chumdari (Universitas Labuhanbatu, 2025)
Scientific literacy is one of the 21st-century skills that students must learn, yet their competence falls short of expectations. Smart Apps Creator (SAC) is an application that provides many features to help teachers construct interactive learning media to increase scientific literacy.Purpose –This research aims to define the profile of students' scientific literacy and assess the needs of SAC media to increase scientific literacy.Methodology – This study employs a mixed method. This study's subjects were sixth-grade primary school pupils and teachers. Data were gathered by test, interview, observation, and documentation methods. The data analysis approach included descriptive statistics and interactive analysis. This research was conducted with the initial step of finding the problem's topic at the research location. Next, the researcher formulated the problem formulation research objectives and created research instruments. After that, the researcher took care of the research permit. After the research permit was approved, the researcher collected the research data. After the research data was obtained, the researcher analyzed and checked the validity or credibility of the data. Then, the researcher drew research conclusions based on the research objectives that had been set at the beginning.Findings –The study's findings reveal the scientific literacy profile of grade VI primary school pupils in the moderate category, and both students and instructors agree that the development of SAC media is necessary to increase scientific literacy.Significance – This study's findings help improve students' scientific literacy skills via SAC media.Keywords:Scientific Literacy, Learning Media, Smart Apps Creator